The Influence of Business Orientation And Company Capabilities On Business Strategy And Its Implications For Business Performance Sustainability in The Fashion Commodity Creative Industry in West Java - Rachmawan, Ahmad; Sudiarti, Nani; Wahyudi, Anang (Dinasti International Journal of Management Science, 2024)
The fashion creative industry is one of the creative industry sectors that continues to grow along with the development of fashion trends, especially in West Java. High competition makes fashion creative businesses face various challenges in achieving the sustainability of their business performance. The right business strategy is needed to compete in a competitive market and the emergence of many new competitors. Based on this background, this study aims to examine the influence of business orientation and company capabilities on business strategy and its implications for business performance sustainability in the fashion commodity creative industry in West Java. The research was conducted on the unit of analysis of fashion commodity creative industry players in West Java in the center of the fashion commodity creative industry with a sample of 200 respondents. The sample was taken by simple random sampling. Data were processed and analyzed using Structural Equation Modeling (SEM). The results showed that business strategy contributes to the sustainability of business performance, where competitive strategy has a greater contribution than competitive strategy. Business strategy is dominantly built by business orientation, which is supported by company capabilities. The results of this study provide theoretical implications in extending the importance of business strategy. Managerially, the results of this study provide implications for fashion commodity creative industry players under business strategies, especially competitive strategies, need to be formulated by improving business orientation and increasing company capabilities.